Pengaruh Konsentrasi Larutan Natrium Klorida (NaCl) Sebagai Bahan Perendam Terhadap Krakteristik Mutu Pati Ubi Talas (Calocasia esculenta L. Schott) - Adi Permana, Kadek Dodik; Hartiati, Amna; Admadi H, Bambang (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 5 No 1 (2017): Maret)
This study aims to 1) the effect of the concentration of sodium chloride (NaCl) as the shredded material to the quality characteristics of potato starch taro 2) determine the concentration of sodium chloride (NaCl) producing quality potato starch taro best quality. This study uses a completely randomized design by treatment with a solution of sodium chloride (NaCl), namely: 2.5%; 5%; 7.5%; 10%; 12.5%; 15% with the addition of water and a comparison of taro yams are:  4 : 1 is repeated 3 times in order to get 18 experimental units. Variables observed were yield, water content, starch content, oxalate content, and multiple comparison test colors. Determining the best treatment is done by testing the effectiveness index. The concentration of sodium chloride (NaCl) very significant effect on the quality characteristics of potato starch on yield, starch content, oxalate content and multiple comparison test color (whiteness), while the quality characteristics taro potato starch does not significantly affect water levels. Starch by treatment with 15% NaCl solution is a treatment that has the best quality starch characteristics, namely, having a yield of 20.22% and a multiple comparison test color of 2.30% (equal whiteness of tapioca flour), water content 7.73% , the starch content of 67.49% and 37,90% oxalate content. Keywords: sodium chloride (NaCl) , starch, taro potato (Calocasia esculenta L. Schott).
Keywords: 130,